Psychological Experience of Humanistic Care Among Medical Staff in Stroke Wards: A Qualitative Research Study Conducted in China - Li, Min; Zhu, Wen-jing; Luo, Qing; Chen, Huang; Duan, Yan; Xie, Hong-zhen (Frontiers in Psychiatry, 2022)
Background As a special patient group, stroke patients have a significant attachment to humanistic care. There are, however, still many problems in clinical practice. Medical staff in stroke wards are the main providers of humanistic care. Finding out the opinions of staff that provide the medical service is vitally important for stroke patients that need access to curative and humanistic care. Objective The aim of the study was to explore the psychological experiences of doctors, nurses and physiotherapists during the implementation of humanistic care in a stroke ward. Method Medical staff including doctors, nurses and physiotherapists were selected from stroke wards in general hospitals (minimum level two) from 13 cities within six provinces in China. A purposive sampling method was used until no new data were generated (n=18). Semi-structured interviews were conducted by using a phenomenological research method. The Colaizzi seven-step method was used for analysis. Result The end user’s experience incorporated four themes: (1) Gradually improving the perception of humanistic caring in a stroke ward. (2) Required improvement of consciousness and ability of humanistic care implementors in a stroke ward. (3) Main problems and contradictions associated with implementing humanistic care in stroke wards. (4) Critical needs of staff in a stroke ward. Conclusion Steady advances have been made in the prevention and treatment of stroke in China. Care behaviour of staff in stroke wards has gradually improved. Nevertheless, while implementing humanistic care in stroke wards, the consciousness and ability of medical staff needs to be improved, in addition to the practical problems and contradictions affecting the development of humanistic care. In order to improve the level of humanistic care in stroke wards, attention should be paid to the overall improvement of the personal qualities of medical staff in stroke wards and the integration of a humanistic management mode.